The occurrence of adverse events following immunization after first and/or second dose of Covishield or Covaxin vaccine at a tertiary care hospital: An observational study - Kumar, Vinay; Kashyap, Vandana; Shenoy, A. G. (International Journal Of Community Medicine And Public Health, 2022)
Background: With the introduction of the COVID-19 vaccine, many cities of India are reporting minor, mild, and severe AEFI cases during half an hour of observation and after that. No vaccine can protect everyone receiving it and is safe too for everyone. Effective vaccines could produce a few unwanted side effects mainly mild and clear up frequently. Methods: After the COVID-19 vaccination, everyone was asked to wait for 30 minutes in the observation room to check for any type of AEFI. While waiting, all second dose beneficiaries were asked to fill a printed case record form with all demographic details, including AEFI events experienced after their first dose of the COVID-19 vaccine. Phone calls were made to all 500 beneficiaries after seven days of vaccination to know about the type of AEFI experienced after the second dose. Results: Safety of product is of paramount importance and in this study, we actively captured adverse events post-vaccination. Fever, headache, weakness, body pain, were the most common adverse events along with pain at the injection site. In our study, the younger age group was associated with minor AEFIs. However, we did not find any supporting evidence for high reactogenicity among women, and this may be due to an almost similar proportion of men and women in our sample. Conclusions: The advantages of immunization in disease prevention have significantly exceeded the risks of immunization-associated adverse events. COVID vaccines have their largest potential to end the COVID-19 pandemic if they are widely accepted and used. As we all want to get rid of the diseases which are not curable easily and spread with very large intensity, now is the time to get vaccinated and control them.